Movement of Atlantic cod around the British Isles: implications for finer scale stock management. Issue 6 (21st October 2014) - Neat, Francis C.; Bendall, Victoria; Berx, Barbara; Wright, Peter John; Ó Cuaig, Macdara; Townhill, Bryony; Schön, Pieter‐Jan; Lee, Janette; Righton, David; Frid, Chris
Summary Commercial fisheries risk unintentionally depleting local population components if stock management units do not reflect the population structure of the species. Atlantic cod Gadus morhua L. was over exploited in the sea areas around the British Isles in the last century and is struggling to recover. There is an urgent need to define the biological stock structure to improve management. In this study, we used data recovered from temperature and depth loggers attached to 252 Atlantic cod to infer and map their movements around the British Isles. Individual cod showed a range of behaviours including migration, site fidelity and limited home ranging. We estimated home ranges and seasonal movements and test predictions based on data from population genetics. Cod from a northern offshore area in the North Sea did not mix with cod from the central and southern North Sea, which in turn did not mix with those from western areas (the Celtic and Irish Seas). Cod experienced average monthly temperatures between 6 and 17 °C and occupied average depths between 15 and 165 m. Cod that occupied the deeper northern offshore area lived in colder and less variable waters than elsewhere. Differences in thermal experience are likely to underpin variation in physiology and growth rate that will have implications for how the species responds to climate change. This study provides evidence that cod living around the British Isles are comprised of at least one more distinct population unit that is currently recognized for stock management purposes. Failure to recognize this complexity of stock structure in past management plans is likely to have been a contributory factor to the over‐exploitation of cod stocks around the British Isles. Synthesis and applications. The results of this study and recent genetic research provide a new and more definitive understanding of movement patterns and population structure of cod around the British Isles. The applied implication of this is that spatially explicit adjustment of exploitation strategies, for example setting a maximum sustainable yield for each of the population units, should be considered to ensure sustainable harvesting of cod in the future.